Peningkatan Pembelajaran Matematika Materi Kesetaraan Nilai Uang Melalui Model Pembelajaran Project Based Learning Bagi siswa Tunagrahita - Oktaviani, Jehan Nabela; Susetyo, Budi; Homdijah, Oom Sitti; Nurhastuti, Nurhastuti; Fitriani, Fitriani; Putri, Tasha Dwilamiisa (Jurnal Pendidikan Kebutuhan Khusus, 2023)
This research aims to improve learning outcomes for class VII SLBN 1 Padang students in learning mathematics regarding the equality of money values through the Problem Based Learning learning model. The classroom action research flow used in this research uses an action research flow divided into four stages, namely planning, implementation, observation and reflection. The method obtained in this research uses qualitative data analysis techniques. The results of this research show that the learning outcomes of students in the learning process using the Problem Based Learning model in mathematics learning material on the equality of the value of money for class VII SMPLB SLB N Padang have increased in each cycle I and cycle So it can be concluded that there has been an increase in learning outcomes in the material on the equality of the value of money with the Problem Based Learning learning model for mentally retarded children